Narrativas de constituição do sujeito na antiguidade e atualidade em Bhagavad-Gita e Ramayan 3392 AD - Lenzi, Rafael Giardini (2014)
From the existential conflict between I vs False ego, as enunciated by ancient mythology, this work investigates the interpretation s possibility of this duality nowadays. This way it is examined on these two temporal contexts the conflict between the man element, or even his soul, often designed as I, and his false ego, or false perception of himself. It starts with the analysis of an antiquity s literary source whose narrative explicitly shows this topic, the Bhagavad-Gita, and sequentially it is taken as object a mediatic verbal-visual-spatial text of the present time, the graphic novel Ramayan 3392 AD. By exploring this question on the first text it is aimed to identify it in the graphic novel, therefore examining the theme s continuity, which according to this point of view is originated in antiquity and kept in nowadays media. Thus it is looked forward to prove this interpretation s possibility in mediatic texts, to prove how this opposition can be considered a connection between different mythologies; and to analyze how the duality is structured at the present times, through comic books research. As important points are considered the changes that occur in the value of sacred, whose investment is existent in the ancient mythology connected to religiosity, but not in comic books generality, not explicitly at least. As theoretical basis to this problematic s analysis on the study corpus, it is used the referential of Greimas discursive semiotics and its development on Landowski s socio-semiotics, while for observations regarding mythologies, beyond these semioticists works and others , it is mainly taken this question s approach by Cassirer. It can be pointed that there is dissolution of the value of sacred, represented in ancient mythology by emphasis and detailing of the mystical and religious theme, while the subject hero s characterization by a duty is kept, in a way that the mystical religious value becomes an ethical value in the nowadays text, being kept in both texts the modalization by should as invariable. Furthermore, mediatic texts bring a differentiated appeal to sensible experience, through plastic components, which alongside with the verbal plane add another meaning s dimension to the narrative; a meaning that is also considered from the ancient text s prescription concerning the existential conflict examined, leading to the formation of a chromatic schematization connected to this opposition. As conclusions it is obtained a possible interpretation of the euphoric subjects as attached to cognitive instances, and of the dysphoric subject as associated to the somatic actancial instance precisely, in an assemblage constitutive of a single macro-subject. From myth to media rises the main change which is the passage from the direct holy s revelation to the detachment of aesthesic sensibility as key piece on the subject s formation. This mechanism allows the sensibility s perception as responsible for making feel the new proposition of the existential conflict that is undeniably of all times